Gamification: software usage ecology - Costa, C. J.; Aparicio, M. (The Online Journal of Science and Technology, 2018)
Gamification is applied in academia and industry and is being studied in the last years. Gamification is nowadays applied to several areas, such as learning, computer science, business, marketing, tourism, among others. Research performed till now suggests that its usage may improve students' and workers' motivation and increase study, productivity and sales. Nevertheless, there are many forms of implementing, according to each industry. Supported in the literature, we identified the game components, game mechanics, and game dynamics, used as part of any gamification implementation. Then, we selected some specific cases in e-learning, computer program learning, open source software development, and crowdsourcing. Finally, we list some of the main software employed in this fields, identifying also implemented features. This allowed us to find the great complexity and variety of implementations. It also enabled us to find ether practitioners or researcher use the word gamification for a broad range of approaches.